Endocrine treatment with 2 years of tamoxifen versus 2 years of exemestane in postmenopausal patients with high-risk early breast cancer and persisting circulating tumor cells: first results of the SUCCESS C endocrine treatment sub-study - Schochter, Fabienne; Rack, Brigitte K.; Tzschaschel, Marie; Polasik, Arkadius; Andergassen, Ulrich; Trapp, Elisabeth; Alunni-Fabbroni, Marianna; Schneeweiss, Andreas; Müller, Volkmar; Pantel, Klaus; Gade, Jörg; Lorenz, Ralf; et al. (Oncology research and treatment, 2018)
Background: ptimal choice and sequence of endocrine treatment following adjuvant chemotherapy in postmenopausal early breast cancer patients are still under discussion and treatment stratification factors are missing. Patients and Methods: Postmenopausal women with HER2-negative, hormone receptor-positive tumors and persisting circulating tumor cells (CTCs; assessed using the FDA-approved CellSearch® System, Janssen Diagnostics, LLC) after chemotherapy were randomized to 2 years of tamoxifen followed by 3 years of exemestane (tamoxifen-exemestane group, n = 54) or 5 years of exemestane (exemestane-only group, n = 54). CTCs were again assessed after the first 2 years of endocrine treatment. In addition, safety data were compared between the 2 groups.Results: The 2 groups were well-balanced with regard to baseline characteristics. The CTC clearance rate after 2 years was 89% in the exemestane-only group and 97% in the tamoxifen-exemestane group (exact Fisher test, p = 0.36). The safety profile showed good tolerability with few grade 3 or 4 adverse events in both groups. Conclusion: The similar CTC clearance rate after 2 years of endocrine therapy with exemestane or tamoxifen, and the safety profiles obtained may indicate comparable efficacy and tolerability of both endocrine treatment regimens. However, these results have to be confirmed by final survival and safety analysis.